Infant-Wrap (InfaWrap) device as pediatric technology tool: The heart rate and SpO2 monitoring for neonates - Mohd Hanafi, Abdul Rahim; Mohd Azrul Hisham, Mohd Adib; Mohamad Zairi, Baharom; Nur Hazreen, Mohd Hasni (Springer, Cham, 2022)
Today, advances in science and technology may contribute to the resolution of medical devices for pediatric. This research focused on the development of the InfaWrap device; a tool to monitor neonate’s heart rate and SpO2. InfaWrap is designed to help the clinicians and parents to observe the baby’s heart rate and oxygen saturation. The InfaWrap device uses a pro mini Arduino as a microcontroller, a MAX30100 oximeter sensor to measure SpO2 and heart rate, and an LM35 to measure body temperature. Besides, we focus on the design and convenience wear criteria, including design characteristics, and structures to ensure the device is lightweight and more comfortable. The proposed InfaWrap device embedded an advanced wireless network sensor system. The data will be appeared in the mobile application installed on the doctor’s or parent’s mobile phone via Bluetooth module. Overall, based on three different babies as a subject in this study, we obtained that he InfaWrap device accuracy results reach the average of 96% for SpO2, 81 bpm for baby heart rate, and 36.4 °C for baby body temperature